2012
DOI: 10.1103/physrevlett.109.267401
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Calculations of Luminescence Spectrum Line Shapes for Defects in Semiconductors: The Example of GaN and ZnO

Abstract: We present a theoretical study of broadening of defect luminescence bands due to vibronic coupling. Numerical proof is provided for the commonly used assumption that a multi-dimensional vibrational problem can be mapped onto an effective one-dimensional configuration coordinate diagram. Our approach is implemented based on density functional theory with a hybrid functional, resulting in luminescence lineshapes for important defects in GaN and ZnO that show unprecedented agreement with experiment. We find clear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
192
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(206 citation statements)
references
References 36 publications
9
192
1
1
Order By: Relevance
“…It has been shown that oxygen vacancies contribute strongly to optical absorption in the visible spectral and are the origin of the red-shi in the PL emission. [51][52][53][54][55] In these previous studies, it has been discussed that the formation energies of intrinsic defects in ZnO, in particular, oxygen vacancies significantly vary, on the other hand, V which is paramagnetic. The line width changes from 3.0 G in the dark to 1.8 G under UV-LED conditions.…”
Section: -50mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that oxygen vacancies contribute strongly to optical absorption in the visible spectral and are the origin of the red-shi in the PL emission. [51][52][53][54][55] In these previous studies, it has been discussed that the formation energies of intrinsic defects in ZnO, in particular, oxygen vacancies significantly vary, on the other hand, V which is paramagnetic. The line width changes from 3.0 G in the dark to 1.8 G under UV-LED conditions.…”
Section: -50mentioning
confidence: 99%
“…Considerable efforts have been made to understand native defects in ZnO by theoretical calculations and experiments, since electronic properties are strongly coupled with the local structure and disorder in crystalline materials. [51][52][53][54][55] However, our focus in this study will be on understanding the charge state of the oxygen vacancy. It has been shown that oxygen vacancies contribute strongly to optical absorption in the visible spectral and are the origin of the red-shi in the PL emission.…”
Section: -50mentioning
confidence: 99%
“…32 We have applied this methodology to barium cerate. Our results for key processes are presented in Table IV, and two important cases are illustrated in Fig.…”
Section: E Optical Propertiesmentioning
confidence: 99%
“…A full description of these processes would involve transitions between vibronic states, and would allow the prediction of luminescence lineshapes. 32 Here, we focus on the most probable radiative transitions, which are represented by the arrows in Fig. 6 and correspond to peaks in absorption or luminescence spectra; these peak energies are listed in Table IV. Kompan et al 9 reported luminescence spectra for BaCeO 3 prepared under various conditions.…”
Section: E Optical Propertiesmentioning
confidence: 99%
“…Calculations of the formation energies and the thermal and optical transition levels of defects are used to assess the potential of solar absorber materials [6][7][8][9] , to predict carrier densities, e.g., in transparent conducting oxides [10][11][12] , and to identify recombination centers 13 . Since the first supercell calculations 14,15 of defect formation energies, the methodology for first principles defect theory has been constantly refined, for example addressing image charge corrections 16,17 , the DFT band gap problem [18][19][20] , defect pairing and clustering 12,21 , as well as vibrational effects 22,23 . However, such supercell defect calculations are generally limited to point defects where either a single or a small number of atoms are added, removed or exchanged around a given lattice site.…”
Section: Pacs Numbersmentioning
confidence: 99%